Se necesitan 10 micros.
En principio, sabemos que 300 pasajeros pueden transportarse en 4 microbuses.
Entonces, el numero de pasajeros que va por cada micro será el cociente entre el numero de pasajeros y el numero de micros:
N = 300/4 = 75
<em>Queremos responder:</em>
¿Cuántos micros se deben aumentar para que por cada 3 micros se transporten 90 pasajeros?
Definamos X como el numero de grupos de 3 micros que tendriamos en esta situación.
Entonces 300 sobre X, debe ser igual a 90 (el numero de pasajeros que va en cada grupo de 3 micros)
300/X = 90
300 = 90*X
300/90 = X = 3.33...
Notar que el número total de micros sera 3 veces X:
3*X = 3*3.33.... = 10
Se necesitan 10 micros.
Si queres leer más sobre el tema, podes ver.
brainly.com/question/23854869
The answer is 1 bc the solution is (1,-3)
Answer:
170°
Step-by-step explanation:
Let a be the distance from Los Angeles to Chicago = 1744 miles, b be the distance from Chicago to New York = 714 miles and c be the distance from New York to Los Angeles = 2451 miles.
A is the angle opposite to side a, B is the angle opposite to side b and C is the angle opposite to side c.
Therefore the angle at Chicago is C.
From cosine rule:
c² = a² + b² - 2ab × cos (C)
2ab × cos (C) = a² + b² - c²
cos (C) = (a² + b² - c²) / 2ab
Substituting:
cos (C) = (1744² + 714² - 2451²) / 2×1744×741
cos (C) = -0.986
C = cos⁻¹ (- 0.986) = 170°
5 (2.3) = 11.5
Hope this helps
Answer:
Simplifying
(4x + -6) = (x + 6y)
Reorder the terms:
(-6 + 4x) = (x + 6y)
Remove parenthesis around (-6 + 4x)
-6 + 4x = (x + 6y)
Remove parenthesis around (x + 6y)
-6 + 4x = x + 6y
Solving
-6 + 4x = x + 6y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-1x' to each side of the equation.
-6 + 4x + -1x = x + -1x + 6y
Combine like terms: 4x + -1x = 3x
-6 + 3x = x + -1x + 6y
Combine like terms: x + -1x = 0
-6 + 3x = 0 + 6y
-6 + 3x = 6y
Add '6' to each side of the equation.
-6 + 6 + 3x = 6 + 6y
Combine like terms: -6 + 6 = 0
0 + 3x = 6 + 6y
3x = 6 + 6y
Divide each side by '3'.
x = 2 + 2y
Simplifying
x = 2 + 2y